IgG/IgM-coated gut microbiota in schizophrenia: associations with inflammation disease activity - Xu, Guohao; Luo, Ruibin; Wu, Ze; Liu, Caihong; Liao, Haipeng; Wu, Junlin; Li, Zhixiang; Wang, Yinmei; Chen, Xi; Li, Yifan; Xu, Ruihuan (Frontiers in Psychiatry, 2026)
BackgroundWhile immunoblobulin A(IgA) dominates gut mucosal immunity, the roles of immunoglobulin M (IgM) and immunoglobulin G (IgG) in host-microbiota interactions remain poorly characterized, particularly in schizophrenia (SCZ). Although gut dysbiosis and immune activation have been implicated in SCZ,the contribution of IgG/IgM-coated gut microbiota to disease associated inflammation and behavioral alterations remains unknown.MethodsWe recruited six patients with SCZ, six with other psychiatric disorders (OPD) and six age- and sex- matched healthy controls. IgG/IgM-coated gut microbiota were isolated from 100 mg fecal samples via magnetic-activated cell sorting (MACS) and profiled by 16S rRNA sequencing. A pilot an IgG/IgM-coated fecal microbiota transplantation (FMT) using anaerobically cultured human intestinal microbiota was conducted in mice to assess the effects on gut pathology, peripheral immunity, and behavior. The percentage of neutrophil granulocyte in peripheral blood was quantified microscopically, and statistical analyses were performed using one-way ANOVA in GraphPad Prism 8, with (p < 0.05.ResultsThe proportions of IgM-coated bacteria was significantly higher in patients with SCZ than in healthy controls (p<0.05), with enrichment of Rhodococcuss, Shigella, Clostridium and Streptococcus. Mice receiving a mixture of high-IgM-coated intestinal bacteria mixture showed reduced depletion of peripheral neutrophils, mild colon shortening, and mucosal inflammation compared with those receiving low IgM-coated or uncoated bacteria. In contrast, high IgG-coated bacteria, enriched in Rhodococcuss, Acinetobater and Pseudomonas, decreased in SCZ, but induced similar inflammatory gut changes. No IgG- nor IgM- induced anxiety-like behavior were detect in the mice.ConclusionsOur findings reveal that IgG/IgM-coated intestinal microbiota display distinct immunoreactive microbiota signatures associated with SCZ. These coated communities promote gut inflammation without inducing anxiety-like behavior, highlighting their potential as novel biomarkers of SCZ-associated immune dysregulation and as targets for personalized therapeutic strategies.